Nocebo Effects on Muscular Performance – An Experimental Study About Clinical Situations - Zech, Nina; Seemann, Milena; Grzesiek, Magdalena; Breu, Anita; Seyfried, Timo F.; Hansen, Ernil (Frontiers in Pharmacology, 2019)
Introduction: Nocebo effects are not only seen in studies of pharmacology and placebo/nocebo research but also in clinical everyday situations. For generation of objective and quantitative data on the impact of negative communication we have evaluated the immediate effects of common sentences, nonverbal signals and situations in the medical context on muscular performance. Methods: In an experimental study, 46 volunteers were tested by dynamometry of the deltoid muscle group to evaluate the maximal muscular strength during arm abduction. Baseline values were compared to performance after exposure to 18 verbal and nonverbal suggestions. Suggestions suspected to be negative were alternated with and compared to positively formulated alternatives. Results: Verbal and nonverbal communication produced significant effects on muscular performance, resulting mainly in weakening. The decrease in muscle strength after risk information for informed consent (91.4% of baseline) was absent, when benefits of the treatment were named coincidently. The weakening effect of asking about „pain“ and „nausea“ (89.4%), and of the announcement of medical interventions (91.7%) could be avoided with alternative wording. Impairment of muscular performance was also observed with the nocebo-inducers negative memory (89.5%) or uncertain future (93.3%), in contrast to a positive memory or the orientation into the presence. Nonverbal suggestions like overhead anesthesia induction (89.9%), a transport in strict flat supine position (89.1%), or a view from the window to a parking lot (94.1%) significantly reduced maximal muscle strength, whereas face-to face induction, half-sitting position and a view into the landscape did not. 8 out of 9 tested clinical situations reduced maximal arm muscle strength significantly, whereas alternative formulations did not. Conclusions: This study describes a quick, simple and uniform test using objective measurement of maximal muscle strength to allow for identification, quantification, and comparison of negative suggestions, regardless of their specific content and effect. Muscle strength is a clinically relevant parameter with regard to early mobilization, risk of falling and sufficient breathing. Furthermore, the observed impairment of muscular performance could reflect a general “weakening effect” of negative suggestions. In addition, the test facilitates development and verification of appropriate alternatives to prevent nocebo effects in patients, thereby improving patient communication.